Lipids as trophic markers in Antarctic krill. III. Temporal changes in digestive gland lipid composition of Euphausia superba in controlled conditions - Alonzo, F; Virtue, P; Nicol, S; Nichols, PD (Marine Ecology Progress Series, 2005)
Two phytoplankton diets with markedly different fatty acid (FA) profiles (thraustochytrid and diatom over a range of concentrations) were fed to juvenile Euphausia superba Dana to evaluate the time lapse required for the development of trophic lipid signatures in the digestive gland (DG). Krill were collected after 5, 10 and 20 d of feeding on thraustochytrids. Krill fed on thraustochytrids for 20 d were also collected after a further 5, 10 and 00 d of feeding on diatoms. An accumulation of polar lipid (0.4 mg per DG) was observed after 5 d of feeding on thraustochytrids at every concentration of food. The deposition of triacylglycerol (0.25 mg per DG) required 10 d of feeding and only occurred at the 2 highest food concentrations. Amounts of thraustochytrid- derived FA, 14:0, 16:0 22:63 and 22:56, increased after 10 d of feeding. The final concentration of 22:63 was dependent on food concentration. Though it was absent in the diet, the essential FA 20:53 accumulated from the retroconversion of 22:63 after 20 d. Changing the krill diet to diatoms resulted in a marked decline in thraustochytrid FA, particularly 14:0 and 22:63, after 5 d, whilst diatom FA, 16:17 and 20:53, remained constant. Thraustochytrid signatures were completely erased from the FA profiles of DG after 20 d feeding on diatoms. Slow accumulation of storage lipid and short residence time of dietary FA suggest that lipid turnover rates are high in Antarctic krill DG. Inter-Research 2005.